The effect of ankle bracing on knee kinetics and kinematics during volleyball-specific tasks - West, T.; Ng, Leo; Campbell, Amity (Wiley-Blackwell, 2014)
The purpose of this study was to examine the effects of ankle bracing on knee kinetics and kinematics during volleyball tasks. Fifteen healthy, elite, female volleyball players performed a series of straight-line and lateral volleyball tasks with no brace and when wearing an ankle brace. A 14-camera Vicon motion analysis system and AMTI force plate were used to capture the kinetic and kinematic data. Knee range of motion, peak knee anterior–posterior and medial–lateral shear forces, and peak ground reaction forces that occurred between initial contact with the force plate and toe off were compared using paired sample t-tests between the braced and nonbraced conditions (P < 0.05). The results revealed no significant effect of bracing on knee kinematics or ground reaction forces during any task or on knee kinetics during the straight-line movement volleyball tasks. However, ankle bracing was demonstrated to reduce knee lateral shear forces during all of the lateral movement volleyball tasks. Wearing the Active Ankle T2 brace will not impact knee joint range of motion and may in fact reduce shear loading to the knee joint in volleyball players.